Interpopulation differences in parasite load and variable selective pressures on MHC genes in Ctenomys talarum - Cutrera, Ana Paula (2014)
We explore potential geographic variation in the pathogen-mediated selective pressures acting on Major Histocompatibility Complex (MHC) loci in the subterranean rodent Ctenomys talarum, evaluating the impact of differences in parasite load between 2 populations (Mar de Cobo [MdC] and Necochea [NC]) on immunogenetic variation and selection on MHC genes in this species. Because Ctenomys from NC face lower parasite load and presumably weaker pathogen-mediated selection on MHC, we expected to find a weaker correlation between MHC variation and parasite load and/or immunocompetence in this population compared to that at MdC. MHC-associated cues are used in other species of rodents as kinship markers to avoid inbreeding, and because kinship structure is less pronounced in NC, we predicted that use of MHC-associated cues in mate choice would be less apparent in this population. We characterized MHC variation in NC as a function of parasite load and immunocompetence and compared our results with previous findings for MdC. The 2 populations were sampled across different, but consecutive, years. Using co-inertia analyses, we found a significant positive association between a specific DRB allele and intensity of infection by fleas in NC. We explored the use of MHC-associated cues in mate choice in NC and found support for both the ?good genes? and the ?genetic compatibility? hypotheses. As expected, associations between MHC and parasite load or immunocompetence were weaker in NC. Evidence indicated that females in NC selected for males with lower MHC diversity. This suggests that parasite-driven selection acting directly on MHC genes seems to be greater for the population facing higher parasite load. However, parasite-driven selection mediated by mate choice may not only be influenced by levels of parasite diversity in the population but also by characteristics of the mating system.